The facilitating effect of connectives across relations and languages - Marchal, Marian; Hewett, Freya; Scholman, Merel C. J.; Shahmohammadi, Sara; Stede, Manfred; Demberg, Vera (Frontiers in Language Sciences, 2025)
The facilitating effect of connectives on discourse processing has been found to be smaller in result relations, compared to other relations (e.g., concession). In addition, connectives are hypothesized to facilitate more in some languages than in others due to typological differences between languages. Speakers of analytic languages (such as English) are assumed to rely more on contextual cues and therefore be less affected by the presence of a connective than speakers of synthetic languages (such as German), who are presumed to rely more on lexical information. We present two self-paced reading studies examining how the effect of a connective depends on the relation type and the language. We find that the presence of a connective facilitates reading more in concession relations than in result relations. This interaction between relation type and relation marking was only found in German.